Pharmacoutilization and adherence to sacubitril/valsartan in real world: the REAL.IT study in HFrEF - Massimo Iacoviello; Gabriele Di Gesaro; Filippo Maria Sarullo; Daniela Miani; Mauro Driussi; Michele Correale; Claudio Bilato; Andrea Passantino; Erberto Carluccio; Alessandra Villani; Luca degliEsposti; Chiara d'Agostino; et al. (ESC Heart Failure, 2024)
Abstract Aims The current European Society of Cardiology (ESC) guidelines provide clear indications for the treatment of acute and chronic heart failure (HF). Nevertheless, there is a constant need for real‐world evidence regarding the effectiveness, adherence, and persistence of drug therapy. We investigated the use of sacubitril/valsartan for the treatment of HF with reduced ejection fraction in real‐world clinical practice in Italy. Methods and results An observational, retrospective, non‐interventional cohort study based on electronic medical records from nine specialized hospital HF centres in Italy was carried out on patients with prescription of sacubitril/valsartan. Overall, 948 patients had a prescription of sacubitril/valsartan, with 924 characterized over 6 months and followed up for 12 months. Pharmacoutilization data at 1 year of follow‐up were available for 225 patients {mean age 69.7 years [standard deviation (SD) = 10.8], 81.8% male}. Of those, 398 (45.2%) reached the target dose of sacubitril/valsartan of 97/103 mg in a mean time of 6.9 (SD = 6.2) weeks. Blood pressure and hypotension in 61 patients (65%) and worsening of chronic kidney disease in 10 patients (10.6%) were the main reasons for not reaching the target dose. Approximatively 50% of patients had a change in sacubitril/valsartan dose during follow‐up, and 158 (70.2%) were persistent with the treatment during the last 3 months of follow‐up. A sensitivity analysis (persistence during the last 4 months of follow‐up) showed persistence for 162 patients (72.0%). Adherence data, available for 387 patients, showed full adherence for 205 (53%). Discontinuation (102/717 patients, 14.2%) was mainly due to hypotension and occurred after a mean time of 34.3 (SD = 28.7) weeks. During follow‐up, out of 606 patients with available data, 434 patients (71.6%) had an HF add‐on drug or drugs concomitant with sacubitril/valsartan. HF‐related hospitalization during follow‐up was numerically higher in non‐persistent (16/67 patients, 23.9%) vs. patients persistent to sacubitril/valsartan (30/158, 19%) (P = 0.405). Conclusions Real‐world data on the use of sacubitril/valsartan in clinical practice in Italy show a rapid titration to the target dose, high therapeutic adherence enabling a good level of therapeutic management in line with ESC guidelines for patients with reduced ejection fraction.